Direct detection of antiprotons with the Timepix3 in a new electrostatic selection beamline - Pacifico, Nicola; Aghion, S.; Alozy, J.; Amsler, C.; Ariga, A.; Ariga, T.; Bonomi, G.; Bräunig, Philippe; Bremer, J.; Brusa, R. S.; Cabaret, L.; Caccia, M.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
We present here the first results obtained employing the Timepix3 for the detection and tagging of annihilations of low energy antiprotons. The Timepix3 is a recently developed hybrid pixel detector with advanced Time-of-Arrival and Time-over-Threshold capabilities and has the potential of allowing precise kinetic energy measurements of low energy charged particles from their time of flight. The tagging of the characteristic antiproton annihilation signature, already studied by our group, is enabled by the high spatial and energy resolution of this detector. In this study we have used a new, dedicated, energy selection beamline (GRACE). The line is symbiotic to the AEgIS experiment at the CERN Antiproton Decelerator and is dedicated to detector tests and possibly antiproton physics experiments. We show how the high resolution of the Timepix3 on the Time-of-Arrival and Time-over-Threshold information allows for a precise 3D reconstruction of the annihilation prongs. The presented results point at the potential use of the Timepix3 in antimatter-research experiments where a precise and unambiguous tagging of antiproton annihilations is required.
Gesehen am 19.10.2020